2018
DOI: 10.1007/s10068-018-0494-y
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus fermentum strains from human breast milk with probiotic properties and cholesterol-lowering effects

Abstract: The study aimed to identify two lactic acid bacteria from human breast milk and evaluate for their probiotic potential. Lactobacillus fermentum strains showed various degree of antibiotic susceptibility profile to clinical commercial antibiotics. The MA-7 and MA-8 strains have never lost their vitality at pH 2 and 3. Lactobacillus fermentum MA-8 exhibited more resistance to 0.3 and 1% bile concentrations than MA-7 strain. Both of the L. fermentum strains can tolerate the simulated gastric and intestinal juices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Many of these bacteria may be human commensals or have potential probiotic effects [1]. Lactic acid bacteria, such as Lactobacillus fermentum, L. gasseri, L. rhamnosus, isolated from human breast milk, can be regarded as potential probiotic bacteria [2][3][4]. Previous studies have suggested that commensal coagulase-negative staphylococci and viridans streptococci found in breast milk can reduce the acquisition of undesired pathogens by infants exposed to hospital environments [5].…”
Section: Introductionmentioning
confidence: 99%
“…Many of these bacteria may be human commensals or have potential probiotic effects [1]. Lactic acid bacteria, such as Lactobacillus fermentum, L. gasseri, L. rhamnosus, isolated from human breast milk, can be regarded as potential probiotic bacteria [2][3][4]. Previous studies have suggested that commensal coagulase-negative staphylococci and viridans streptococci found in breast milk can reduce the acquisition of undesired pathogens by infants exposed to hospital environments [5].…”
Section: Introductionmentioning
confidence: 99%
“…(2018) [25] observed 100% survivability for breast milk isolates even after 4h of exposure to one percent bile salt.…”
Section: Probiotic Properties Of the Isolate 321 Acid And Bile Tolerancementioning
confidence: 99%
“…Apart from L. reuteri , Lactobacillus fermentum strains from human milk have been studied as probiotic candidates, and proved to be safe, well tolerated and useful for the prophylaxis against community-acquired infections [ 171 ]. They also showed cholesterol-lowering effects in simulated models of liver and gastrointestinal tract [ 172 ]. Both L. fermentum , and another milk-derived species, Lactobacillus salivarius , enhanced both natural and acquired immune responses, via activation of natural killer and T cell subsets and induction of a broad array of cytokines in peripheral blood mononuclear cells in vitro [ 173 ].…”
Section: A Focused Insight Into Human Milk Microbiotamentioning
confidence: 99%